Retrospective study of canine leishmaniosis in Israel - Gad Baneth; Michal Peri Markovich; Yaarit Nachum-Biala; Daniel Yasur-Landau; Monica Leszkowicz Mazuz; Charles L. Jaffe (Parasites & Vectors)
Abstract Background Canine and human leishmaniasis are prevalent around the Mediterranean Basin, where dogs are considered to be the main peridomestic reservoir for human disease. Canine leishmaniosis was initially diagnosed in central Israel in 1994. Since then, it has been routinely detected in the canine population of Israel, while only a very small number of human cases are reported annually. Methods This retrospective analysis of dogs diagnosed with Leishmania infection at the Hebrew University from 1994 to December 2023 included 658 dogs. Results Although infected dogs were reported in all 16 subdistricts of Israel, the geographic distribution and locations of infected dogs focused mainly on central and northern Israel. From 2020, isolated cases have also been detected in southern Israel, suggesting a southward spread of disease. A majority of infected dogs (n = 341, 51.8%) were residents of rural localities, with the remainder (n = 267, 40.6%) present in urban areas. The highest number of cases was found in the Jerusalem Subdistrict, but the highest density of infected dogs, cases per square km, was present in the Tel Aviv Subdistrict. The incidence rate of clinical leishmaniosis for the years 2007–2023, based on the Israeli dog registry, ranged from 0.03 to 0.09 per 1000 registered dogs. Of the 353 dogs diagnosed from 2013 onward, age ranged from 3 months to 14.5 years with a median of 4.5 years. Of the 38 dogs who were also tested by polymerase chain reaction (PCR) for Leishmania spp. since 2010, 32 (84%) were infected by L. infantum, 4 (11%) with L. tropica, and 2 (5%) with L. major. Conclusions The epidemiology of canine leishmaniosis caused mostly by L. infantum presents a contrary picture to that of human leishmaniasis in Israel, in which more than 99% of patients are reported to have cutaneous leishmaniasis caused mostly by L. major and L. tropica, and less than 1% have visceral disease due to L. infantum. The widespread presence of canine L. infantum infection in central and northern Israel constitutes a zoonotic reservoir for disease for humans, wildlife, cats, and other dogs. Graphical Abstract